Precipice : a novel - Harris, Robert, 1957- (Harper, an imprint of HarperCollinsPublishers, 2024)
"Summer 1914. A world on the brink of catastrophe. In London, twenty-six-year-old Venetia Stanley--aristocratic, clever, bored, reckless--is part of a fast group of upper-crust bohemians and socialites known as "The Coterie." She's also engaged in a clandestine love affair with the Prime Minister, H. H. Asquith, a man more than twice her age. He writes to her obsessively, sharing the most sensitive matters of state. As Asquith reluctantly leads the country into war with Germany, a young intelligence officer with Scotland Yard is assigned to investigate a leak of top-secret documents. Suddenly, what was a sexual intrigue becomes a matter of national security that could topple the British government--and will alter the course of political history."--